Principle of intellectualization of engineering education in the light of requirements of Bolonian Convention - Bila, Galina; Ponomareva, Iryna; Antraptseva, Nadia (My University, 2011)
Formation of a single educational space in Europe - it is a reality, without which it is impossible to reform and implement the strategy of development of higher education in Ukraine. The dynamic development of the world community, the introduction of new technologies requires constant student mastering and improving knowledge of proper intellectual development, communication skills, independent and creative approach to decision-making, building information and social skills. Формирование единого образовательного пространства в Европе - это реальность, без которой невозможно реформировать и воплощать в жизнь стратегию развития высшего образования Украины. Динамичное развитие мирового сообщества, внедрение новейших технологий требует от студента постоянного усвоения и совершенствования знаний, надлежащего интеллектуального развития, коммуникативных способностей, самостоятельного и творческого подхода к принятию решений, формирования информационных и социальных навыков. Формування єдиного освітнього простору в Європі — це реальність, без якої неможливо реформувати і втілювати в життя стратегію розвитку вищої освіти України. Динамічний розвиток світової спільноти, запровадження новітніх технологій вимагає від студента постійного засвоєння та вдосконалення знань, належного інтелектуального розвитку, комунікативних здібностей, самостійного та творчого підходу до прийняття рішень, формування інформаційних та соціальних навичок.
Keywords: єдиний освітній простір в Європі; новітні технології; комунікативні здібності; творчий підхід; single educational space in Europe; the latest technology; communication skills; creativity; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів